Effects of Digital Activism on Brand Awareness and Image - Malambo, Nachanza (University of the Witwatersrand, Johannesburg, 2022)
The purpose of this research paper is to explore the impact that digital activism has on brands in South Africa. Digital activism, commonly known by social media users as cancel culture, has gained momentum with social media audiences; using the network effects of popular platforms such as Twitter, YouTube, Facebook and Instagram to discipline users, brands and celebrities that may have erred or offended users. As brands observe the increase of hours spent on social media, they are likely to increase their presence on the platforms of choice either for digital advertising and marketing communication purposes or to connect with potential audiences. They may be caught up in incidents of digital activism as has been seen with brands such as H&M, Dove, Tresemme and Clicks in recent years in South Africa. This paper begins by unearthing the roots of digital activism in political sciences disciplines and explores how the brand management theories of brand image and brand awareness are affected by this activity. The research problem explores the fact that traditional marketers have concentrated on the positive brand building elements of brand equity, with attention given to the awareness and image that brands are able to conjure in the minds of consumers; without much focus on the negative elements of brand avoidance, hate, and aversion, which can be outcome of digital activism. The research objectives were firstly to investigate the impact that social media activity has on brands as it has been shown that an increase of social media usage among individuals would increase the interaction that brands have with their intended target audience and members of the community. Secondly, the study sought to investigate the impact that digital activism has on brand awareness as one of the gaps to be studied is on the negative impact that digital activism or cancel culture may have on brand awareness. Thirdly, the researchers examined the impact of digital activism on brand avoidance, as a deliberate effort to avoid the brand either online or physically. Lastly, the study seeks to investigate the impact that digital activism has on a brands image, on whether this is reduced or increased in the light of increased mentions, trends, or appearances on popular social media platforms
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, WireDSpace, University of the Witwatersrand, Johannesburg, 2022
Keywords: Brand awareness; Brand image; Digital activism; Cancel culture; Social media; UCTD; SDG-9: Industry, innovation and infrastructure